Progression of glucose‐lowering diabetes therapy in TECOS. Issue 1 (22nd December 2018) - Bethel, M. Angelyn; Engel, Samuel S.; Stevens, Susanna R.; Lokhnygina, Yuliya; Ding, Jie; Josse, Robert G.; Alvarsson, Michael; Hramiak, Irene; Green, Jennifer B.; Peterson, Eric D.; Holman, Rury R.
Summary: Aims: TECOS was a randomized, double‐blind, placebo‐controlled trial assessing the impact of sitagliptin vs. placebo on cardiovascular outcomes when added to usual care in patients with type 2 diabetes. We report the use of concomitant diabetes medications and the risk for progression to insulin during follow‐up. Materials and Methods: TECOS enrolled 14 671 participants with HbA1c 6.5%‐8.0% on monotherapy with metformin, pioglitazone, sulfonylurea (SU), or dual therapy with two oral agents or insulin with or without metformin. Subsequent diabetes management was by the participant's usual care physician. Time to initiation of insulin and risk of hypoglycaemia were estimated using Cox proportional hazards models. Results: The most common glucose‐lowering regimens at baseline were metformin monotherapy (30.2%), SU monotherapy (8.5%), metformin/SU therapy (35.1%), and insulin with or without metformin (13.9% and 8.6%, respectively). Over a median 3.0 years' follow‐up, diabetes therapy was intensified in 25.2% of participants (sitagliptin 22.0%, placebo 28.3%). Medications most commonly added were SU (8.3%) or insulin (8.8%). Insulin initiation in the usual care setting occurred at mean (standard deviation) HbA1c of 8.5 (1.5)%. Sitagliptin did not impact rates of severe hypoglycaemia, but delayed progression to insulin when added to metformin or metformin/SU regimens. Conclusion: Consistent with the trial's pragmatic design, TECOS participants underwent typical progression of diabetes medications. Sitagliptin was associated with lower HbA1c, without increased risk for severe hypoglycaemia and was associated with delayed progression to insulin when added to metformin with or without SU. Abstract : The TECOS study assessed the impact of sitagliptin compared to placebo on cardiovascular outcomes in 14 671 participants with type 2 diabetes over a median duration of 3 years. During the study, diabetes therapy was intensified in 25.2% of participants, most commonly by the addition of a sulfonylurea or insulin. A delay in the progression to insulin was observed in sitagliptin‐treated participants who entered the study on metformin or metformin/sulfonylurea treatment